Efficient Uptake of Recombinant Lipidated Survivin by Antigen-Presenting Cells Initiates Antigen Cross-Presentation and Antitumor Immunity - Chiang, Chen-Yi; Chen, Yi-Jyun; Wu, Chiao-Chieh; Liu, Shih-Jen; Leng, Chih-Hsiang; Chen, Hsin-Wei (Frontiers in Immunology, 2018)
Survivin is over-expressed in various types of human cancer, but rarely expressed in terminally differentiated adult tissues. Thus, survivin is a potential target antigen for a cancer vaccine. However, self-tumor associated antigens are not highly immunogenic. Bacteria derived lipoproteins can activate antigen-presenting cells through their toll-like receptors to enhance immune responses. In this context, lipidated survivin is an attractive candidate for cancer immunotherapy. In the present study, recombinant lipidated human survivin (LSur) was prepared from an Escherichia coli-based system. We investigated whether LSur is efficiently captured by antigen presenting cells then facilitating effective induction of survivin cross-presentation and generation of immunity against cancer cells. Our results demonstrate that LSur, but not its non-lipidated counterpart, can activate mouse bone marrow derived-dendritic cells (BMDCs) to enhance cytokine (IL-6, TNF-α, and IL-12) secretion and co-stimulatory molecules (CD40, CD80, CD86 and MHC II) expression. However, the pathways involved in the capture of the recombinant lipidated antigen by antigen-presenting cells have not yet been elucidated. To this end, we employ various endocytosis inhibitors to study the effect on LSur internalization. We show that the internalization of LSur is suppressed by the inhibition of various routes of endocytosis. These results suggest that endocytosis of LSur by BMDCs can be mediated by multiple mechanisms. Furthermore, LSur is trafficked to the early endosome after internalization by BMDCs. These features of LSur are advantageous for cross-presentation and the induction of antitumor immunity. We demonstrate that immunization of C57BL/6 mice with LSur under treatment with exogenous adjuvant-free formulation induce survivin-specific CD8+ T-cell responses and suppress tumor growth. The antitumor responses are mediated by CD8+ cells. Our findings indicate that LSur is a potential candidate for stimulating protective antitumor immunity. This study suggests that lipidated tumor antigens may be a promising approach for raising a robust antitumor response in cancer immunotherapy.